2021
DOI: 10.1097/opx.0000000000001722
|View full text |Cite
|
Sign up to set email alerts
|

Association between Clinical Vision Measures and Visual Perception and Soccer Referees' On-field Performance

Abstract: SIGNIFICANCEThe decisions taken by soccer officials are critically important to game management. Understanding the underlying processes that mediate expert performance in soccer refereeing may lead to a better standard of officiating. Vision is the dominant source of incoming information upon which officials rely to make their on-field decisions.PURPOSEWe tested the hypothesis that performance on generic tests of vision and visual perception predicts domain-specific performance in elite-level soccer referees (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Soccer referees and assistant referees with abnormal color vision may be at a disadvantage because of diminished color contrast between the player clothes and green grass. Because of the importance of color vision in referees, given the fact that the soccer field is green, and in the case of red or green jerseys, it can lead to arbitrary mistakes( 18 ) ( 27 , 28 ). The study by Buys and Ferreira indicated that most of the athletes 79.9%) did not have a color deficiency ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soccer referees and assistant referees with abnormal color vision may be at a disadvantage because of diminished color contrast between the player clothes and green grass. Because of the importance of color vision in referees, given the fact that the soccer field is green, and in the case of red or green jerseys, it can lead to arbitrary mistakes( 18 ) ( 27 , 28 ). The study by Buys and Ferreira indicated that most of the athletes 79.9%) did not have a color deficiency ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the neuro-ophthalmic principles may be integrated with longstanding knowledge structures to amplify decision-making skills on the field. In a similar vein of research, Baptista et al found that after adjusting for experience and demographic factors in soccer officials, stereoacuity and visual memory were the factors that were associated with superior on-field performance [ 55 ]. It was also found that roughly a quarter of elite soccer officials in a study had vision that could be capable of improved visual acuity while officiating.…”
Section: Physiology Of Neuro-ophthalmic Principles For 3d Virtual On-...mentioning
confidence: 99%
“…Another area of emphasis addressed in this feature issue is the comparison of visual skills between athletes (and referees) across different levels of expertise and across different ages 5–12 . This includes several original investigations comparing differing levels of expertise, 5,6,11 as well as a review by Dalton 7 that addresses the quiet eye phenomena.…”
mentioning
confidence: 99%
“…Another area of emphasis addressed in this feature issue is the comparison of visual skills between athletes (and referees) across different levels of expertise and across different ages. [5][6][7][8][9][10][11][12] This includes several original investigations comparing differing levels of expertise, 5,6,11 as well as a review by Dalton 7 that addresses the quiet eye phenomena. This influential concept refers to "the final fixation or tracking gaze prior to the onset of a critical motor action," which has been shown to correlate with performance and overall expertise in athletes.…”
mentioning
confidence: 99%